In Situ/Operando Raman Techniques in Lithium–Sulfur Batteries. Issue 3 (6th February 2022) - Xue, Lanxin; Li, Yaoyao; Hu, Anjun; Zhou, Mingjie; Chen, Wei; Lei, Tianyu; Yan, Yichao; Huang, Jianwen; Yang, Chengtao; Wang, Xianfu; Hu, Yin; Xiong, Jie
Abstract : Tremendous efforts have been made to fulfill the promises of lithium–sulfur (Li–S) battery as the candidate for next‐generation energy storage devices. However, challenges such as capacity degradation and dendrite growth still remain, hampering the commercialization of Li–S batteries. Different from the conventional ion‐insertion‐based lithium battery, the electrochemical and chemical processes in the cathode of Li–S battery are based on extremely complex conversion reactions. Together with the uncontrollable hostless lithium deposition process on the anode side, the future development of Li–S batteries faces great difficulty and requires deeper understanding of the fundamental mechanism. Herein, the recent applications of in situ/operando Raman techniques for monitoring the real‐time variations in Li–S batteries are summarized to reveal the reaction mechanism and guide the design of strategies for improving the battery performances. The design concepts and advantages of in situ/operando Raman studies are highlighted, and the future explorations based on such technique are discussed, aiming to accelerate the development progress of Li–S battery for practical applications. Abstract : The recent applications of in situ/operando Raman techniques for monitoring the real‐time variations in lithium–sulfur(Li–S) batteries are summarized. The design concepts and advantages of in  situ/operando Raman studies are highlighted, and the future explorations based on such technique are discussed, aiming to accelerate the development progress of Li–S battery for practical applications.